Sex differences in anaerobic performance in CrossFit athletes: a comparison of three different all-out tests. - Ponce-García, Tomás; García-Romero, Jerónimo; Carrasco-Fernández, Laura; Castillo-Domínguez, Alejandro; Benítez-Porres, Javier (Peer J., 2025)
Background: Athletic performance can be influenced by various factors, including those related to biological sex. Various scientific disciplines have studied the observed differences in athletic performance between men and women. Moreover, anaerobic performance refers to the capacity of the human body to generate energy quickly and efficiently during high-intensity and short-duration activities. It is associated with the ability to perform explosive actions and the capacity for rapid recovery between repeated efforts. Anaerobic performance is a determining factor for performance in high-intensity sports and those with predominantly lower intensity but intermittent peaks of higher intensity. One high-intensity sport that has experienced exponential growth and attracts increasing numbers of participants yearly is commercially known as CrossFit (CF). Therefore, the primary purpose of this study was to determine the anaerobic performance differences between sexes in CF athletes in terms of absolute and relative values. Methods: A cross-sectional study was conducted over 2 weeks. Fifty CrossFit athletes (25 men and 25 women) voluntarily participated in the study. They were subjected to body composition analysis and three maximal effort tests to measure anaerobic performance: a cycle ergometer test, a continuous jump test and a squat test. Results: Significant differences were found in all the variables of absolute peak power and relative to body mass in the three tests. In values adjusted to lean and muscle mass, significant differences were only found in the cycle ergometer test but not in the other two. In mean power variables, significant differences were found in all the variables studied, except for the mean power adjusted to muscle mass in the squat test. In conclusion, this study’s results indicate that differences between sexes in absolute and relative peak powers measured in all test...
Keywords: Ejercicio físico; Entrenamiento deportivo - Aspectos fisiológicos; Cuerpo humano - Composición; Diferencias sexuales; Sports performance; Body composition; Athletes; CrossFit; High-intensity functional training